Testing the Roles of Distribution and Alternation in Phonological Relationships*. (July 2016) - Lu, Yu-An
This study investigates how two factors, distribution and morphological alternation, affect speakers' ability to group sounds into the same phoneme category. Previous findings indicate that allophonic variants of a single phoneme are rated as more similar than sounds belonging to separate phonemes. The present study builds on these findings by conducting a similarity rating task to investigate the processing of anterior and posterior coronal sibilants [s] and [ɕ/ʃ] in three languages in which the two sounds participate in different types of relationships: (i) English, in which [s] and [ʃ] occur in the same environment (e.g. see versus she ); (ii) Korean, in which [s] and [ɕ] are in complementary distribution and participate in regular and productive morphological alternations; and (iii) Mandarin, in which [s] and [ɕ] are in complementary distribution but do not participate in morphological alternations due to its phonotactic restrictions. The results showed that both English and Mandarin speakers rated the anterior versus posterior coronal sibilants as more different than Korean speakers did, suggesting that the Mandarin speakers, who have access only to distributional evidence, are less likely to treat the two sounds as members of a single category than the Korean speakers, who are exposed to evidence from both distribution and morphological alternation.